2024
DOI: 10.1146/annurev-psych-032323-051354
|View full text |Cite
|
Sign up to set email alerts
|

Music Training and Nonmusical Abilities

E. Glenn Schellenberg,
César F. Lima

Abstract: Music training is generally assumed to improve perceptual and cognitive abilities. Although correlational data highlight positive associations, experimental results are inconclusive, raising questions about causality. Does music training have far-transfer effects, or do preexisting factors determine who takes music lessons? All behavior reflects genetic and environmental influences, but differences in emphasis—nature versus nurture—have been a source of tension throughout the history of psychology. After revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 346 publications
0
15
0
Order By: Relevance
“…More fundamentally, association does not establish causation: people with innately more resilient behavioural regulation and social cognition circuitry might be more likely to learn a musical instrument, or continue listening regularly to music. The socio-emotional benefits of musical training remain poorly understood, and causal relations could be further investigated with alternative indices of musicality and prospective longitudinal studies ( 11 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…More fundamentally, association does not establish causation: people with innately more resilient behavioural regulation and social cognition circuitry might be more likely to learn a musical instrument, or continue listening regularly to music. The socio-emotional benefits of musical training remain poorly understood, and causal relations could be further investigated with alternative indices of musicality and prospective longitudinal studies ( 11 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Music training -is "group or individual lessons with a teacher, focused on learning how to sing and/or play a musical instrument" (Schellenberg and Lima, 2024). Many researchers argue that music training enhances not only music-related skills in preschool children (Münte et al, 2002), but also plays a major role in the development of personality (Savenkova, 2023), cultural learning (Ķestere, 2017;Klimova, 2023), and aesthetic upbringing (Volkova and Shestovskaya, 2021;Ailamazyan, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers argue that music training enhances not only music-related skills in preschool children (Münte et al, 2002), but also plays a major role in the development of personality (Savenkova, 2023), cultural learning (Ķestere, 2017;Klimova, 2023), and aesthetic upbringing (Volkova and Shestovskaya, 2021;Ailamazyan, 2023). Arguing in favor of a far transfer from music training to cognitive functioning remains difficult (Schellenberg and Lima, 2024). The cognitive ability for which an impact of music training makes the most intuitive sense is EF (Schellenberg and Lima, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, musical training is believed to enhance various cognitive and emotional abilities, including verbal memory, fluency, perception, creativity, spatial skills, IQ scores, and empathy [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, after evaluating evidence produced by other researchers, Schellenberg and Lima [ 13 ] concluded that causal inferences cannot be made. Specifically, these authors suggested that there is no conclusive evidence to support the claim that music training has far-reaching cognitive benefits that can be generalised to other domains, which is consistent with the findings obtained from other types of training.…”
mentioning
confidence: 99%
“…Specifically, these authors suggested that there is no conclusive evidence to support the claim that music training has far-reaching cognitive benefits that can be generalised to other domains, which is consistent with the findings obtained from other types of training. Nevertheless, Schellenberg and Lima [ 13 ] advocated for music to be included in school curricula and funded research due to its intrinsic value.…”
mentioning
confidence: 99%